RARE-12. EARLY FOCAL RADIOTHERAPY AND TEMOZOLOMIDE FOLLOWING COMPLETE RESECTION APPEAR SUPERIOR TO INTENSIVE CHEMOTHERAPY IN CHILDREN WITH EMBRYONAL TUMORS WITH MULTILAYERED ROSETTES (ETMR). (11th November 2019) - Slavc, Irene; Mayr, Lisa; Gojo, Johannes; Peyrl, Andreas; Azizi, Amedeo; Dieckmann, Karin; Haberler, Christine; Czech, Thomas
Abstract: BACKGROUND: Embryonal tumor with multilayered rosettes (ETMR) is an extremely rare entity characterized by LIN28A expression and alterations in the C19MC locus. ETMRs predominantly occur in young children and have a dismal prognosis. We report on our single institution experience in seven consecutive patients. METHODS: Between 2006 and 2016, seven patients were diagnosed with ETMR. Diagnosis was established prospectively by characteristic histopathologic features, LIN28A immunostaining and amplification of the C19MC region in five patients and retrospectively confirmed in two additional patients originally diagnosed as central nervous system primitive neuroectodermal tumor. Tumor location was supratentorial in all patients. Median age at diagnosis was 25 months (range 5–38). Male to female ratio was 1:6. RESULTS: All patients received gross total tumor resection and four patients were treated with intensive chemotherapy regimens including high-dose chemotherapy in three patients. Four patients recurred after a median of 6 months (range 2–11 months) and all except one patient who died after high-dose chemotherapy, succumbed to their disease after a median of 13 months (range 7–28 months). Consequently, the two most recent patients were treated with gross total tumor resection, primary focal radiotherapy and concomitant temozolomide followed by temozolomide for one year. Due to the high risk of leptomeningeal dissemination intraventricular chemotherapy was administered to all except one patient. Both patients who were treated with primary focal radiotherapy are in continuous complete remission 41 and 36 months after diagnosis. CONCLUSION: Gross total resection followed by early focal radiotherapy, temozolomide, and intrathecal chemotherapy seem to be superior to intensive chemotherapy including high-dose chemotherapy.